The Influence of E-Learning towards Students’ Heutagogy Skills in Higher Education - Nuansa Bayu Segara; Agus Suprijono; Katon Galih Setyawan (Jurnal Pendidikan dan Pengajaran, 2021)
Heutagogy skills are needed by students to take part in the e-learning process during the Covid-19 pandemic. This study examines the measurement model and proved the influence of e-learning towards self-directed, self-regulated, and self-determined learning skills. This research uses a survey method, the data is collected through an online questionnaire which shared with 232 respondents. The research instrument validity was tested by Confirmatory Factor Analysis (CFA) and reliability test by calculating Cronc’bach value. Path Analysis with AMOS 21.0 was used to analyze the relationship between variables. The result confirms that e-learning significantly affected self-regulated learning. Meanwhile, self-regulated learning has a significant effect on self-determined. Path analysis result indicated that e-learning significantly affected self-determined learning if self-directed and self-regulated learning is first developed. The results of this study also provided an empirical basis for other researchers who want to develop independent learning in students through e-learning. Indicators in self-directed learning can be developed in an online learning process, hence, it can be observed directly on student learning outcomes.